On $(n,m)-$Groups for $n>2m$ - Galić, Radoslav (Sarajevo Journal of Mathematics, 2024)
In this article a theorem about a $(2m,m)-$group of Čupona-Dimovski is generalized. 2000 Mathematics Subject Classification. Primary: 20N15.